Circadian Regulation of Macronutrient Absorption. (December 2015) - Hussain, M. Mahmood; Pan, Xiaoyue
Various intestinal functions exhibit circadian rhythmicity. Disruptions in these rhythms as in shift workers and transcontinental travelers are associated with intestinal discomfort. Circadian rhythms are controlled at the molecular level by core clock and clock-controlled genes. These clock genes are expressed in intestinal cells, suggesting that they might participate in the circadian regulation of intestinal functions. A major function of the intestine is nutrient absorption. Here, we will review absorption of proteins, carbohydrates, and lipids and circadian regulation of various transporters involved in their absorption. A better understanding of circadian regulation of intestinal absorption might help control several metabolic disorders and attenuate intestinal discomfort associated with disruptions in sleep-wake cycles.